Exponential stability for a transmission problem with distributed delay (Nonlinear Studies, 2025)
In this paper, we consider a transmission problem in a bounded domain with a distributed delay in the two equations. Under suitable assumption on the weight of the delay, we establish an exponential decay result for the energy by introducing suitable energy and Lyapunov functional.